Chitosan characteristics in electrolyte solutions: Combined molecular dynamics modeling and slender body hydrodynamics. (15th September 2022) - Lupa, Dawid; Płaziński, Wojciech; Michna, Aneta; Wasilewska, Monika; Pomastowski, Paweł; Gołębiowski, Adrian; Buszewski, Bogusław; Adamczyk, Zbigniew
Abstract: Molecular dynamics modeling was applied to predict chitosan molecule conformations, the contour length, the gyration radius, the effective cross-section and the density in electrolyte solutions. Using various experimental techniques the diffusion coefficient, the hydrodynamic diameter and the electrophoretic mobility of molecules were determined. This allowed to calculate the zeta potential, the electrokinetic charge and the effective ionization degree of the chitosan molecule as a function of pH and the temperature. The chitosan solution density and zero shear dynamic viscosity were also measured, which enabled to determine the intrinsic viscosity increment. The experimental results were quantitatively interpreted in terms of the slender body hydrodynamics exploiting molecule characteristics derived from the modeling. It is also confirmed that this approach can be successfully used for a proper interpretation of previous literature data obtained under various physicochemical conditions. Graphical abstract: Unlabelled Image